Effectiveness of Community-based Interventions in Improving the Oral & Dental Health of the Elderly People: A Systematic Review and Meta-analysis - Saber Azami-Aghdash; Fatemeh Pournaghi-Azar; Mahdi Nouri; Mohammad Mohseni; Mir Hossein Aghaei (Journal of Holistic Nursing and Midwifery)
Introduction: Considering the rapid growth in the number of aged people and their oral & dental health problems, there is a need for effective community-based interventions to improve their oral health. Objective: This study aims to investigate the effectiveness of community-based interventions in improving the oral & dental health of elderly people. Materials and Methods: This is a systematic review and meta-analysis. The related studies published from January 2000 to March 2023 were searched in PubMed, Scopus, Cochrane Oral Health’s Trials Register, and Web of Science databases. The risk of bias in the included studies was assessed using the Cochrane tool. Results: Nineteen articles were included in the review. Interventions were divided into four groups: educational interventions, oral & dental health care interventions, chewing gum, and combined interventions. A total of 95 indicators were examined in the studies, 53 of which were not statistically significant. Regarding the overall effectiveness of the interventions, 10 studies reported them as completely effective, 5 studies as relatively effective, and 4 as ineffective. Chewing gum had the highest effectiveness. The results of the meta-analysis showed that the mean difference in the dental plaque index between the intervention and control groups was -0.65 (95% CI; -2.03%, 0.74%, Q=59.6, df=5, P=0.001, I2=97.8%) the mean difference in the denture plaque index was -0.20 (95% CI; -0.38%, -0.02%, Q=3.22, df=3, P=0.36, I2=21.3%), and the mean difference in the gingival index was -0.36 (95% CI; -0.99%, 0.27%; Q=5.2, df=1, P=0.02, I2=80.9%). Conclusion: There are no clear advantages or evidence about the effectiveness of community-based interventions in improving the oral & dental health of elderly people.